Theories of Haitian Mobility and their Relationship to the Dominican Sugar Industry - Juliana Ramirez (Caribbean Studies Students' Union, 2015)
Theories of Haitian Mobility and their Relationship to the Dominican Sugar Industry by Juliana Ramirez.pdf